2016
DOI: 10.1016/j.jtcms.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Current anti-diabetes mechanisms and clinical trials using Morus alba L.

Abstract: Backgrounds: Diabetes mellitus, especially type 2 diabetes, with its fast-rising

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(47 reference statements)
0
14
0
3
Order By: Relevance
“…1-dexoynojirimycin (DNJ), flavonoids and polysaccharides from mulberry leaf are validated to have hypoglycemic effect through inhibition of α-glucosidase [3]. Mulberry leaf extract could increase insulin sensitivity by activating phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT) signalling pathway via the translocation of the glucose transporter 4 (GLUT4) to the plasma membrane and the increase in expressions of pancreatic duodenal homeobox-1 (PDX-1), insulin-1, and insulin-2 in the pancreas, and correct the imbalance of glucose metabolism by activating AMP-activated protein kinase (AMPK) signalling with the uptake of 3-O-methyl-D-glucose transport [4]. Mulberry leaf could attenuate IR by enhancing the expression of the peroxisome proliferator-activated receptor γ (PPARγ), and it also could reduce oxidative stress and suppress the apoptosis of β-cell and nuclear factor kappa B (NF-κB) signalling pathway to improve IR [4].…”
Section: Introductionmentioning
confidence: 99%
“…1-dexoynojirimycin (DNJ), flavonoids and polysaccharides from mulberry leaf are validated to have hypoglycemic effect through inhibition of α-glucosidase [3]. Mulberry leaf extract could increase insulin sensitivity by activating phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT) signalling pathway via the translocation of the glucose transporter 4 (GLUT4) to the plasma membrane and the increase in expressions of pancreatic duodenal homeobox-1 (PDX-1), insulin-1, and insulin-2 in the pancreas, and correct the imbalance of glucose metabolism by activating AMP-activated protein kinase (AMPK) signalling with the uptake of 3-O-methyl-D-glucose transport [4]. Mulberry leaf could attenuate IR by enhancing the expression of the peroxisome proliferator-activated receptor γ (PPARγ), and it also could reduce oxidative stress and suppress the apoptosis of β-cell and nuclear factor kappa B (NF-κB) signalling pathway to improve IR [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mori Folium (MF), known as Sangye (Pinyin name) in Chinese, is the dried leaf derived from Morus alba L., which has been widely used for more than 1000 years in Chinese medicine clinics and other Asian countries (Tian et al, 2016 ). According to Chinese Pharmacopeia (2015 version), MF is yearly harvested at the First Frost and recognized as an edible herb with the function of clearing heat and eliminating cough as well as invigorating liver and improving eyesight in combination with other herbs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in cells and animal studies, it was found that preparations and active compounds from Morus sp. have inhibitory effects on gene expression of all regulatory GNG enzymes, including phosphoenolpyruvate carboxykinase (PEPCK) [133,134].…”
Section: Effects On Glucose Homeostasis In the Livermentioning
confidence: 99%